Windshield for vehicle and production method of the same
By forming a compressed stress portion at the terminal junction through surface polishing and plastic deformation, the method addresses the thermal stress issues caused by lead-free solder, enhancing the durability of vehicle windshields.
Patent Information
- Application Number
- JP2023116528
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
The use of lead-free solder in joining conductors to glass plates in vehicle windshields results in higher thermal stress and reduced destruction intensity due to the mismatch in thermal expansion coefficients, leading to potential cracking and reduced durability.
A method involving the formation of a compressed stress portion at the terminal junction using lead-free solder, achieved through surface polishing and plastic deformation of the conductor area, reducing voids and glass frit components to enhance the structural integrity.
The method increases the destruction intensity of the glass plate after terminal attachment, minimizing cracking and enhancing durability by applying compression stress to the terminal junction, thereby improving the structural integrity of the windshield.
Smart Images

Figure 2025014197000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to vehicle windshields and methods of manufacturing the same. [Background technology]
[0002] For window glass of a vehicle such as an automobile, a laminated glass in which a plurality of glass plates are bonded together or a tempered glass is preferably used. In general, a glass plate as a material for a vehicle windshield has a light-shielding layer formed in a peripheral region and is processed into a shape having a curved surface by thermoforming. Also, there is known a vehicle windshield that includes an electrical function part or a conductor connected to the electrical function part and a power supply member such as a harness and a cable. Examples of the electrical function part include a heating wire, an electric heating layer, an antenna, a light control layer, a light emitting element, and combinations thereof.
[0003] For example, in the case of a windshield, an electric heating wire or layer may be formed on the lower and side edges of the windshield to melt frost, snow, ice, etc. that has adhered to the wipers and prevent the wipers from freezing. In addition, an optical device including an optical device such as an ADAS (Advanced Driver Assistance systems) camera, LiDAR (Light Detection And Ranging), radar, and optical sensor that acquires information in front of the vehicle for autonomous driving and prevention of collision accidents, and a housing called a bracket or the like that houses the optical device may be installed on the inner surface of the windshield. In such a configuration, in order to improve the sensing accuracy of the optical device, an electric heating wire or an electric heating layer may be formed on the glass part in front of the optical device to prevent fogging and frost. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-18932 [Patent Document 2] International Publication No. 2006 / 132319 Summary of the Invention [Problem to be solved by the invention]
[0005] The conductor can be formed, for example, by applying and firing a silver-containing paste containing silver powder and glass frit. The firing of the silver-containing paste can be carried out simultaneously with the thermoforming of the glass sheet. In this specification, a glass sheet having an electric conductor is referred to as a "glass sheet with an electric conductor".
[0006] Conventionally, the electric conductor and the power supply member are joined by using solder. The electric conductor preferably includes a power supply portion for supplying power to the electrical function portion. Conventionally, for example, a terminal is fixed to the tip of a power supply member such as a wire harness, and this terminal is joined to a conductor (preferably a power supply part included in the conductor) using solder. There are lead solder and lead-free solder. In recent years, there has been concern about the impact of lead on the environment, and legal restrictions on lead solder are becoming more widespread, so there is a demand for high-quality production technology using lead-free solder. To bond a conductor and solder well, it is necessary to form an alloy layer at the bonding interface between the conductor and solder, which contains an alloy of one or more metal elements contained in the conductor and multiple metal elements contained in the solder. To achieve this, it is necessary to heat the solder to above its melting point.
[0007] When the above-mentioned solder bonding is performed on the glass sheet with conductor, localized high-temperature heating and cooling from high temperature to room temperature occur. During cooling, a difference in the amount of thermal contraction occurs between the glass sheet and the solder due to the difference between the thermal expansion coefficient of the glass sheet and the thermal expansion coefficient of the solder, causing distortion between the glass sheet and the solder, and generating stress (specifically, tensile stress) in the glass sheet with conductor. This stress may remain after cooling. This residual stress may cause cracks in the glass sheet with conductor after window glass is manufactured.
[0008] Generally, the melting point of lead-free solder is higher than that of lead-containing solder, for example, about 220°C, and solder bonding must be performed at a higher temperature (for example, about 300°C). Therefore, when lead-free solder is used, the glass plate with conductor is subjected to a larger thermal load in terms of temperature and time, and a larger stress is generated. In addition, since lead-free solder does not contain lead, which has a low elasticity, it has a higher elasticity and is less likely to deform than lead-containing solder, so that the stress generated with temperature change is less likely to be alleviated. For these reasons, problems such as residual stress after bonding and the resulting cracking after manufacturing can occur, especially when lead-free solder is used.
[0009] If the breaking strength of the glass sheet after terminal attachment is low, cracks may occur when an external force is applied to the glass sheet. In particular, when a terminal is joined to a power supply part formed on a light-shielding layer using lead-free solder, the breaking strength of the glass sheet after terminal attachment tends to decrease. It is preferable to increase the breaking strength of the glass sheet after terminal attachment in soldering using lead-free solder while designing the conductor so that it is difficult for people outside the vehicle to see. In this specification, the "breaking strength before or after terminal attachment" refers to the load at which glass breaks when a load is applied to the glass before or after terminal attachment, and can be measured by the method described in the Examples section below.
[0010] In Patent Document 1, A glass plate module to which wiring for supplying power can be joined, A glass plate and A heating wire disposed on the glass sheet; a power supply unit that is disposed on the glass plate, connected to the wiring, and supplies power to the heating wire; the power supply unit is formed by a conductive print mainly composed of metal particles (preferably silver or copper particles) having a thermal expansion coefficient larger than that of the glass plate; A glass plate module is disclosed in which the thickness of the power supply part is thinner than the thickness of the heating wire (claims 1 and 21). The glass sheet module may further include a solder (preferably lead-free solder) disposed on the power supply portion, and a terminal fixed to the power supply portion via the solder (claims 23 and 25).
[0011] Patent Document 1 describes (paragraph 0108) that by making the thickness of the power supply part thinner than the heating wire, the tensile stress generated in the glass sheet can be reduced, and cracks in the glass sheet and the power supply part can be suppressed. Patent Document 1 also describes a method for improving the printing method of the conductive print, making the thickness of the power supply part thinner than the heating wire during the printing process of the conductive print (paragraphs 0117 and 0118).
[0012] In Patent Document 2, The glass plate has a conductive coating mainly composed of silver formed on the surface thereof, and a terminal connected to the conductive coating via solder. A glass article is disclosed in which the proportion of cavities per unit area in a cross section of the conductive coating at least at the portion where the terminal is joined is 10% or less (Claim 1). Patent Document 2 also makes no mention of lead-free solder, but does state (paragraph 0015) that according to the above embodiment, it is possible to improve the bonding strength when a terminal is bonded to a conductive coating via solder.
[0013] Patent Document 2 also discloses a method for manufacturing a glass article, which comprises printing a paste, the paste being prepared by adding 1 to 5 mass % of an organic medium based on the total mass of a silver paste, onto one main surface of a glass plate, forming a conductive coating by firing, and bonding a terminal onto the conductive coating (Claim 3). Patent Document 2 also discloses a method for producing a conductive coating, which includes a first step of printing a paste containing silver particles and glass frit onto a glass plate, a second step of subjecting the paste to a drying treatment involving heating, and a third step of heating the glass plate that has been subjected to the drying treatment to fire the conductive coating (Claim 4).
[0014] However, Patent Documents 1 and 2 do not describe or suggest an embodiment in which at least the surface of the terminal joint is a compressive stress portion, or a preferable stress value of the compressive stress portion.
[0015] The present disclosure has been made in consideration of the above circumstances, and aims to provide a vehicle windshield that includes a portion in which a conductor and a terminal are joined using lead-free solder and that can increase the breaking strength after the terminals are attached, and a manufacturing method thereof. [Means for solving the problem]
[0016] The present disclosure provides the following vehicle windshields and methods for manufacturing the same [1] to
[15] . [1] Includes laminated glass in which multiple glass sheets are bonded together via an interlayer film, The laminated glass is a vehicle windshield comprising: the glass plate; a terminal-attached glass plate having a conductor formed on one surface of the glass plate, the conductor being made of a material containing silver and glass frit and having a terminal joint portion to which a terminal is joined; and a terminal joined onto the terminal joint portion of the conductor via lead-free solder; the electrical conductor includes an electrical function or is electrically connected to an electrical function; the conductor includes a power supply portion for supplying power to the electrical function portion, the power supply portion including the terminal joint portion; At least a surface of the terminal joint portion is a compressive stress portion.
[0017] [2] The compressive stress portion is measured using a micro X-ray stress measuring device. 2 A vehicle windshield as set forth in [1], having a stress value measured by the ψ method of -20 MPa or less. [3] The compressive stress portion is measured using a micro X-ray stress measuring device. 2 [2] A vehicle windshield having a stress value measured by the ψ method of -50 to -20 MPa.
[0018] [4] The vehicle windshield according to any one of [1] to [3], wherein the conductor has a polished portion on a surface of a region including the terminal joint portion. [5] The vehicle windshield of [4], wherein the conductor has a non-polished portion on a surface in an area not including the terminal joint. [6] The glass plate with terminals has a light-shielding layer between the glass plate and the terminal joint portion of the conductor, The vehicle windshield according to any one of [1] to [5], wherein the light-shielding layer contains a black pigment and a glass frit.
[0019] [7] A vehicle windshield according to any one of [1] to [6], wherein the glass plate with terminal has an exposed portion that is not covered by the glass plate facing the terminal with the intermediate film interposed therebetween, the conductor is formed on the intermediate film side of the glass plate with terminal, and the terminal connection portion of the conductor is formed in the exposed portion of the glass plate with terminal.
[0020] [8] The vehicle windshield according to any one of [1] to [6], wherein in the laminated glass, the conductor is formed on the side of the glass plate with terminals opposite to the interlayer film side. [9] The glass plate with terminals has, in a plan view, an optical device mounting region in which an optical device is mounted, a light-transmitting portion located within the optical device mounting region and through which incident light from the outside to the optical device and / or emitted light from the optical device passes, and a light-shielding layer surrounding at least a portion of the light-transmitting portion in a plan view, [8] The vehicle windshield, wherein the conductor includes a heating wire formed inside the translucent portion, the power supply portion formed outside the translucent portion, and connection wiring formed outside the translucent portion and connecting the heating wire and the power supply portion.
[0021]
[10] The vehicle windshield according to any one of [1] to [9], wherein a power supply member made of a round wire or foil-shaped conductor is fixed to the terminal.
[0022]
[11] A step (S2) of applying a silver-containing paste containing silver and glass frit, which are materials for the conductor, onto the glass plate, which is a material for the glass plate with terminals; A step (S3) of firing the glass plate coated with the material for the conductor to form the conductor including the terminal joint portion; A step (S5) of plastically deforming at least a surface of a region including the terminal joint portion of the conductor; and (S6) joining the terminal via lead-free solder onto the terminal joining portion, at least the surface of which has been plastically deformed.
[0023]
[12] The method for manufacturing a vehicle windshield according to
[11] , wherein step (S5) is a step of polishing a surface of a region including the terminal joint of the conductor.
[0024]
[13] In the laminated glass, the glass plate with terminal has an exposed portion that is not covered by the glass plate facing the intermediate film via the intermediate film, the conductor is formed on the glass plate with terminal on the intermediate film side, and the terminal connection portion of the conductor is formed on the exposed portion of the glass plate with terminal, The method for producing a vehicle windshield according to
[11] or
[12] , further comprising, between the step (S3) and the step (S5), a step (S4) of bonding the plurality of glass plates together via the intermediate film.
[0025]
[14] In the laminated glass, the conductor is formed on a side of the glass plate with terminals opposite to the interlayer film, The method for producing a vehicle windshield according to
[11] or
[12] , further comprising, between the step (S3) and the step (S5), a step (S4) of bonding the plurality of glass plates together via the intermediate film.
[0026]
[15] The glass plate with terminals has a light-shielding layer between the glass plate and the terminal joint portion of the conductor, Prior to the step (S2), a step (S1) is provided for applying a ceramic paste containing a black pigment and a glass frit, which are materials for the light-shielding layer, onto the glass plate, which is a material for the glass plate with terminals; The method for manufacturing a vehicle windshield according to any one of
[11] to
[14] , wherein in step (S3), a material for the light-shielding layer is fired to form the light-shielding layer. Effect of the Invention
[0027] In the vehicle windshield of the present disclosure, at least the surface of the terminal joint portion is a compressive stress portion. According to the present disclosure, it is possible to provide a vehicle windshield that includes a portion in which a conductor and a terminal are joined using lead-free solder and that can increase the breaking strength after the terminals are attached, and a method for manufacturing the same. [Brief description of the drawings]
[0028] [Figure 1] 1 is an overall plan view of a vehicle windshield according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a partially enlarged plan view of FIG. [Diagram 3] FIG. 3 is a cross-sectional view taken along line III-III in FIG. [Figure 4] FIG. 4 is a partially enlarged cross-sectional view of FIG. [Figure 5A] FIG. 2 is a process diagram of a method for manufacturing a vehicle windshield according to the first embodiment. [Figure 5B] FIG. 2 is a process diagram of a method for manufacturing a vehicle windshield according to the first embodiment. [Figure 5C] FIG. 2 is a process diagram of a method for manufacturing a vehicle windshield according to the first embodiment. [Figure 5D] FIG. 2 is a process diagram of a method for manufacturing a vehicle windshield according to the first embodiment. [Figure 6] FIG. 4 is a cross-sectional view showing a design modification example of the first embodiment. [Figure 7A] FIG. 4 is an overall plan view of a vehicle windshield according to a second embodiment of the present invention. [Figure 7B] FIG. 7B is a partially enlarged plan view of FIG. 7A. [Figure 8] 8 is a cross-sectional view taken along line VIII-VIII in FIG. 7B. [Figure 9A] 6A to 6C are process diagrams of a method for manufacturing a vehicle windshield according to a second embodiment. [Figure 9B] 6A to 6C are process diagrams of a method for manufacturing a vehicle windshield according to a second embodiment. [Figure 9C] 6A to 6C are process diagrams of a method for manufacturing a vehicle windshield according to a second embodiment. [Figure 10A] 1 is an image showing an example of measuring the porosity of a conductor without polishing. [Figure 10B] 1 is an image showing an example of measuring the porosity of a polished conductor. [Figure 10C] 1 is an image showing an example of measuring the porosity of a polished conductor. [Figure 11A] 1 is a graph showing the evaluation results of Examples 41 to 45. [Figure 11B] 1 is a graph showing the evaluation results of Examples 41 to 45. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Generally, thin film structures are called "films" and "sheets" depending on their thickness. In this specification, there is no clear distinction between them. Therefore, in this specification, "film" may include "sheets". In this specification, the term "approximately" attached to a shape means a shape that has been partially changed, such as a chamfered shape with rounded corners, a shape with part of the shape missing, or a shape with an arbitrary small shape added to the shape. In this specification, unless otherwise specified, the term "surface of a glass plate" refers to a main surface having a large area, excluding the end faces (also called side faces) of a glass plate. In this specification, unless otherwise specified, "up and down," "left and right," "vertical and horizontal," and "inside and outside" refer to the state in which the vehicle windshield is fitted into the vehicle (actual state of use). In this specification, "lead-free solder" refers to solder that is substantially free of lead, and the lead content in lead-free solder is 500 ppm or less. In this specification, unless otherwise specified, when lead-free solder is described as being "substantially free of a certain metal element other than lead," it means that the content of that metal element is 1000 ppm or less. In this specification, unless otherwise specified, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. Hereinafter, an embodiment of the present invention will be described.
[0030] [Vehicle windshield and its manufacturing method] The present disclosure relates to a vehicle windshield including a laminated glass in which a plurality of glass sheets are bonded together via an interlayer film, and a method for manufacturing the same. In this specification, unless otherwise specified, "glass sheet" refers to untempered glass.
[0031] The type of glass plate that is the material of the laminated glass is not particularly limited, and examples thereof include soda lime glass, borosilicate glass, aluminosilicate glass, lithium silicate glass, quartz glass, sapphire glass, and non-alkali glass.
[0032] The thickness of the laminated glass is not particularly limited, and is preferably 2 to 6 mm for use as a vehicle windshield. When the laminated glass is composed of two glass sheets, the thickness of the glass sheet on the inside of the vehicle and the thickness of the glass sheet on the outside of the vehicle may be the same or different. The thickness of the glass sheet on the inside of the vehicle is preferably 0.3 to 2.3 mm. If the thickness of the glass sheet on the inside of the vehicle is 0.3 mm or more, the handling property is good, and if it is 2.3 mm or less, the mass is not too large. The thickness of the glass sheet on the outside of the vehicle is preferably 1.0 to 3.0 mm. If the thickness of the glass sheet on the outside of the vehicle is 1.0 mm or more, the strength of the performance of resistance to flying stones and the like is sufficient, and if it is 3.0 mm or less, the mass of the laminated glass is not too large, which is preferable in terms of fuel efficiency of the vehicle. If the thickness of the glass sheet on the outside of the vehicle and the thickness of the glass sheet on the inside of the vehicle are both 1.8 mm or less, the laminated glass can be made both lightweight and soundproof, which is preferable.
[0033] The vehicle windshield may have a curved shape such that the vehicle exterior side is convex when installed in the vehicle. When the vehicle windshield is a laminated glass, the glass sheet on the vehicle interior side and the glass sheet on the vehicle exterior side may both have a curved shape such that the vehicle exterior side is convex. The vehicle windshield may have a single curved shape curved only in one direction, either the left-right direction or the up-down direction, or a compound curved shape curved in both the left-right direction and the up-down direction. The radius of curvature of the vehicle windshield may be 2000 to 11000 mm. The radius of curvature of the vehicle windshield in the left-right direction and the up-down direction may be the same or different. Gravity forming, press forming, roller forming, etc. are used for bending the vehicle windshield.
[0034] The laminated glass may have a functional film having functions such as water repellency, low reflectivity, low radiation, ultraviolet ray shielding, infrared ray shielding, and coloring, on at least a partial region of the surface. The laminated glass may have, in at least a partial region inside, a functional film having functions such as low reflectivity, low emissivity, ultraviolet shielding, infrared shielding, coloring, etc. At least a partial region of the interlayer film of the laminated glass may have functions such as ultraviolet shielding, infrared shielding, coloring, etc. The interlayer of the laminated glass may be a single layer or a laminated layer.
[0035] The laminated glass may have a light-shielding layer in a predetermined region of the surface. The light-shielding layer can be formed by a known method, for example, by applying a ceramic paste containing a black pigment and glass frit to a predetermined region of the surface of a glass plate, which is the material of the laminated glass, and firing the applied layer. The thickness of the light-shielding layer is not particularly limited, and is, for example, 5 to 20 μm. The light-shielding layer can be formed in the peripheral region of any surface of the laminated glass. For example, the light-shielding layer can be formed in the peripheral region of the glass plate on the inside of the vehicle and / or the surface on the inside of the glass plate on the outside of the vehicle.
[0036] In the present disclosure, a laminated glass includes a glass sheet, a terminal-attached glass sheet having a conductor formed on one surface of the glass sheet and made of a material containing silver and glass frit, the conductor having a terminal joint to which a terminal is joined, and a terminal joined onto the terminal joint of the conductor via lead-free solder. In this specification, the "terminal joint" of a conductor refers to the portion of the conductor directly below the lead-free solder.
[0037] The electrical conductors may be formed directly on and in contact with the surface of the glass sheet, or may be formed on any component formed on the surface of the glass sheet. The electric conductor may be formed on the interlayer film side of the terminal-equipped glass plate, or on the side of the terminal-equipped glass plate opposite to the interlayer film side. The glass plate with terminals may have a light-shielding layer between the glass plate and the terminal joint of the conductor. In this case, the conductor may be formed on the light-shielding layer formed on the glass plate.
[0038] The conductor having the terminal joint is formed by applying a silver-containing paste containing silver powder and glass frit onto a glass plate and firing the paste. The thickness of the conductor is not particularly limited and is, for example, 5 to 20 μm, preferably 5 to 10 μm.
[0039] The silver-containing paste contains silver powder and glass frit, and may further contain a vehicle and additives as necessary.
[0040] The silver powder is composed of particles containing silver and / or a silver alloy. The content of the silver powder in the silver-containing paste is preferably 65 to 85 mass%, more preferably 75 to 85 mass%, and particularly preferably 80 to 85 mass%. If the content of the silver powder is within this range, the resistivity of the conductor can be easily adjusted within a suitable range. The average particle size of the silver powder is preferably 0.1 to 10 μm, more preferably 0.1 to 7 μm. If the average particle size of the silver powder is within this range, the resistivity of the conductor can be easily adjusted within a suitable range. In this specification, unless otherwise specified, the "average particle size of silver powder" refers to the average particle size (D50) measured by a laser scattering particle size distribution analyzer.
[0041] Examples of the glass frit include Bi2O3-B2O3-SiO2-based glass frit and B2O3-SiO2-based glass frit. The content of the glass frit in the silver-containing paste is preferably 2 to 10 mass%, more preferably 3 to 8 mass%. If the content of the glass frit is 2 mass% or more, the conductor is easily sintered, and if it is 10 mass% or less, the resistivity of the conductor is easily adjusted within a suitable range.
[0042] Examples of the vehicle include resin solutions in which binder resins such as ethyl cellulose resin, acrylic resin, and alkyd resin are dissolved in solvents such as α-terpineol, butyl carbitol acetate, and ethyl carbitol acetate. The content of the vehicle in the silver-containing paste is preferably 10 to 45% by mass, and more preferably 15 to 25% by mass.
[0043] Examples of additives include resistance adjusters such as Ni, Al, Sn, Pt, and Pd; colorants such as V, Mn, Fe, Co, Mo, and compounds thereof. The content of the additives in the silver-containing paste (the total amount when multiple types are used) is preferably 2% by mass or less, more preferably 1% by mass or less.
[0044] The electrical conductors may include an electrical function or be electrically connected to an electrical function. The electrical functional portion may include one or more heating wires, heating layers, antennas, dimming layers, light-emitting elements, and combinations thereof. Light-emitting elements may include LEDs (Light Emitting Diodes) and OLEDs (Organic Light Emitting Diodes). The one or more electric heating wires or layers can remove and prevent fog, frost, snow, ice, etc. The one or more electric heating wires or layers can be used, for example, to prevent windshield wipers from freezing; to improve the sensing accuracy of optical devices, including optical instruments such as cameras and radars; etc. The electrical functional portion can be manufactured by a known method.
[0045] The conductor may include a power supply portion for supplying power to the electrical function portion, and the power supply portion may include a terminal junction portion. The power supply portion may include a pair of power supply electrodes (also called a pair of bus bars), and each of the power supply electrodes may include a terminal junction portion. For example, one of the power supply electrodes is a positive electrode and is connected to a power source or a signal source provided in the vehicle via a power supply member, and the other power supply electrode is a negative electrode and is connected to the vehicle body (earth) via a power supply member. Note that the number of power supply electrodes for the positive electrode may be one or more, and the number of power supply electrodes for the negative electrode may be one or more. When the conductor is connected to the electrical function unit, the conductor and the electrical function unit may be formed on the same glass surface or on different glass surfaces.
[0046] A power supply member made of a round or foil conductor can be fixed to the terminal. In this specification, the term "conductor" includes a covered conductor in which one or more conductors are covered with an insulating material. A covered conductor is preferable as the power supply member. Specific examples of the power supply member include a harness and a cable. Examples of the round conductor include a wire harness. Examples of the foil conductor include a flat harness and a flexible printed circuit board. The power supply member has an exposed conductor portion, and the terminal is fixed to the exposed conductor portion. The material of the exposed conductor portion is not particularly limited, and examples thereof include Cu, Al, Ag, Au, Ti, Sn, Zn, alloys thereof, and combinations thereof. The exposed conductor portion may be a main metal whose surface is plated with another metal. The exposed conductor portion may have a thin oxide film on its surface.
[0047] Lead-free solder is solder that contains little or no lead, and known solders can be used. Examples of lead-free solder include SnAg-based solders that contain Sn and Ag; SnAgCu (SAC)-based solders that contain Sn, Ag, and Cu; SnZnBi-based solders that contain Sn, Zn, and Bi; SnCu-based solders that contain Sn and Cu; SnZnAl-based solders that contain Sn, Zn, and Al; and In-based solders that contain In.
[0048] From the viewpoint of environmental resistance, etc., preferred lead-free solders include, for example, SnAg-based lead-free solders that contain Sn and Ag and are substantially free of Sb, Cu and In; and SnAgCu (SAC)-based lead-free solders that contain Sn, Ag and Cu and are substantially free of Sb and In. The melting point of lead-free solder such as SnAg-based and SnAgCu-based solder is higher than that of leaded solder, for example, about 220° C. When lead-free solder such as SnAg-based and SnAgCu-based solder is used, the solder bonding temperature is, for example, about 300° C. The present disclosure is particularly effective when lead-free solder such as SnAg-based and SnAgCu-based solder with a high melting point is used.
[0049] Preferred embodiments of the SnAg-based and SnAgCu-based lead-free solders will be described below. The Sn content in the SnAg-based and SnAgCu-based lead-free solders is not particularly limited, and is preferably 95% by mass or more, more preferably 95 to 98.5% by mass, and particularly preferably 96 to 98% by mass. If the Sn content is 95% by mass or more (the Ag content is 5% by mass or less), the melting point of the lead-free solder can be relatively low, so that the soldering temperature can be relatively low and the temperature rise of the glass plate can be relatively small. As a result, the residual stress generated in the glass plate and the resulting cracking of the glass plate can be suppressed.
[0050] Generally, when using Sn-based lead-free solder that does not contain Ag, the Sn in the lead-free solder and the Ag in the conductor are highly compatible, so the Ag in the terminal joint of the conductor is likely to penetrate into the lead-free solder containing Sn, which is known as "silver erosion." In this case, the terminal joint may discolor due to deterioration and thinning, resulting in poor appearance. When lead-free solder containing Sn and Ag is used, the Sn in the lead-free solder has already formed a compound with Ag, which prevents the Ag in the terminal joint of the conductor from penetrating into the lead-free solder, thereby preventing discoloration of the terminal joint and the resulting poor appearance. The Ag content in the lead-free solder is preferably 1.5 to 5 mass%, more preferably 2 to 4 mass%. If the Ag content is 1.5 mass% or more, the penetration of Ag in the terminal joint of the conductor into the lead-free solder can be effectively suppressed, and good joint strength can be obtained. If the Ag content is 5 mass% or less, the material cost of the lead-free solder can be kept low, and the melting point of the lead-free solder can be kept relatively low.
[0051] The lead-free solder may contain Cu as a metal element other than Sn and Ag. The amount of Cu contained in the lead-free solder is not particularly limited, and is preferably 1 mass % or less, and more preferably 0.5 mass % or less. An example of the composition of SnAg-based lead-free solder is Sn: 98% by mass, Ag: 2% by mass, etc. An example of the composition of SnAgCu-based lead-free solder is Sn: 96.5% by mass, Ag: 3.0% by mass, Cu: 0.5% by mass, etc.
[0052] From the viewpoint of reducing thermal stress on the glass plate when terminals are attached, an In-based lead-free solder containing In, which is a low melting point solder, is also preferable. As for In-based lead-free solder, SnIn-based lead-free solder containing Sn and In and substantially free of Sb, Ag and Cu; SnAgIn based lead-free solder containing Sn, Ag and In, and substantially free of Sb, Cu, Bi, Ni and Zn; SnAgInCu based lead-free solder containing Sn, Ag, In and Cu, and substantially free of Sb, Bi, Ni and Zn; SnAgInBi based lead-free solder containing Sn, Ag, In and Bi, and substantially free of Sb, Cu, Ni and Zn; Examples of such lead-free solder include SnAgInNiCuZn-based lead-free solders that contain Sn, Ag, In, Ni, Cu and Zn and are substantially free of Sb and Bi.
[0053] The present disclosure provides a vehicle windshield that includes a portion where a conductor and a terminal are joined using lead-free solder and that can increase the breaking strength after the terminals are attached, and a method for manufacturing the same.
[0054] As explained in the section [Problems to be Solved by the Invention], generally, when a glass sheet with a conductor is soldered, localized heating to a high temperature and cooling from the high temperature to room temperature occur, and stress may remain after cooling. This residual stress may cause cracks to occur in the glass sheet with a conductor after the window glass is manufactured. Generally, the melting point of lead-free solder is higher than that of lead-containing solder, so when lead-free solder is used, a larger stress is generated in the glass plate with conductor. Furthermore, since lead-free solder does not contain lead, which has a low elastic modulus, it has a higher elastic modulus and is less likely to deform than lead-containing solder, so the generated stress is less likely to be alleviated. For these reasons, problems such as residual stress after joining and the resulting cracking after manufacturing can occur, especially when lead-free solder is used. If the breaking strength of the glass plate after the terminals are attached is low, the glass plate may break when an external force is applied to the glass plate. In particular, when the terminals are joined to the power supply part formed on the light-shielding layer using lead-free solder, the breaking strength of the glass plate after the terminals are attached tends to decrease.
[0055] According to the research of the present inventors, the following has been found. The coefficient of linear expansion (CTE) of a glass plate is, for example, 90×10 -7 / ℃. If necessary, the coefficient of linear expansion (CTE) of the light-shielding layer formed between the glass plate and the terminal joint is, for example, 70 to 80 × 10 -7 / °C. In general, the coefficient of linear expansion (CTE) of the light-shielding layer is smaller than the coefficient of linear expansion (CTE) of the glass plate, so that the stress remaining in the light-shielding layer in the conductor-attached glass plate obtained after forming a ceramic paste layer and a silver-containing paste layer on the glass plate, firing at a high temperature, and cooling to room temperature is compressive stress. The coefficient of linear expansion (CTE) of the conductor including the terminal joint is, for example, 180×10 -7 / °C. In general, the coefficient of linear expansion (CTE) of a conductor including a terminal junction is larger than the coefficient of linear expansion (CTE) of a glass plate, so that in a glass plate with a conductor obtained after forming a ceramic paste layer and a silver-containing paste layer on a glass plate, firing at a high temperature, and cooling to room temperature, the stress remaining in the conductor including the terminal junction is tensile stress.
[0056] By plastically deforming at least the surface of the terminal joint, at least the surface of the terminal joint can be made into a compressive stress portion to which compressive stress is applied. The surface or surface layer is plastically deformed and stretched, while the deeper portion returns to its original shape by elastic deformation, which is thought to impart compressive stress to at least the surface of the conductor. As a method for plastically deforming at least the surface of the terminal joint, surface polishing or the like can be mentioned.
[0057] According to the inventor's research, it has been found that when tensile stress is applied to the terminal joint, the breaking strength of the glass plate after the terminals are attached tends to decrease, whereas when compressive stress is applied to the terminal joint, the breaking strength of the glass plate after the terminals are attached can be improved. The surface layer of the conductor can be, for example, in the range of about 3 to 5 μm deep from the outermost surface of the conductor. Due to the relationship between the coefficient of linear expansion (CTE) of each material, the conductor is pulled by the solder when soldered. If the conductor has compressive stress, the conductor is prevented from being pulled by the solder, and residual tensile stress in the glass sheet with terminals obtained after soldering is prevented, which is thought to improve the breaking strength of the glass sheet with terminals. If the thickness of the conductor is about 5 to 20 μm, the entire terminal joint portion of the conductor can be made into a compressive stress portion by a method such as surface polishing. Incidentally, Patent Documents 1 and 2 cited in the section "Background Art" do not state or suggest an embodiment in which at least the surface of a terminal joint is a compressive stress portion, or a preferred stress value of the compressive stress portion.
[0058] The vehicle windshield of the present disclosure comprises: The laminated glass includes a plurality of glass sheets bonded together via an interlayer film, The laminated glass includes a glass sheet, a terminal-attached glass sheet having a conductor formed on one surface of the glass sheet and made of a material containing silver and glass frit, the conductor having a terminal joint to which a terminal is joined, and a terminal joined onto the terminal joint of the conductor via lead-free solder. In the vehicle windshield of the present disclosure, The conductor includes an electrical function or is electrically connected to an electrical function; The electrical conductor includes a power supply portion for supplying power to an electrical function portion, and the power supply portion includes a terminal joint portion. In the vehicle windshield of the present disclosure, at least the surface of the terminal joint portion is a compressive stress portion to which compressive stress is applied. According to the present disclosure, it is possible to provide a vehicle windshield that includes a portion in which a conductor and a terminal are joined using lead-free solder, and that can increase the breaking strength after the terminals are attached.
[0059] The stress value of the conductor was measured using a micro-part X-ray stress measuring device, and the sin 2 It can be measured by the ψ method. The diffraction angle 2θ is measured while changing the angle ψ between the normal to the sample surface and the normal to the lattice surface. The relationship between the stress value σ, the angle ψ between the normal to the sample surface and the normal to the lattice surface, and the diffraction angle 2θ is expressed by the following formula.
[0060]
number
[0061] (x,y)=(sin 2 ψ, 2θ) data is plotted, and the slope of the obtained approximation line is Δ(2θ) / Δ(sin 2 ψ) data. This Δ(2θ) / Δ(sin 2The stress value σ can be calculated by multiplying the data for ψ) by the stress constant K, which is determined by the material. Note that a negative sign for the stress value indicates compressive stress, and a positive sign for tensile stress.
[0062] In this specification, unless otherwise specified, the "stress value of a conductor" is measured using a micro X-ray stress measuring device. 2 This is a stress value measured by the ψ method, and is determined by the method described in the Examples section below. The stress value of the compressive stress portion may be a negative value, and is preferably -20 MPa or less. The upper limit is more preferably -25 MPa, and particularly preferably -30 MPa. The lower limit is not particularly limited, and is, for example, -50 MPa or -45 MPa.
[0063] As described above, one method for plastically deforming at least the surface of the terminal joint is surface polishing. In the vehicle windshield of the present disclosure, the electric conductor may have a polished portion having a polished surface in a region including the terminal joint, and at least the surface of the polished portion may be a compressive stress portion. The electric conductor may have a non-polished portion having an unpolished surface in a region not including the terminal joint. The polished portion can have a smaller porosity than the non-polished portion whose surface is not polished. The porosity of the polished portion is preferably smaller, and is preferably 10% or less, more preferably 8% or less, particularly preferably 7% or less, and particularly preferably 3% or less. The lower limit of the porosity of the polished portion is, for example, 0.5%. The porosity of the non-polished portion is greater than the porosity of the polished portion and may be more than 10% or less than 10%, for example, 15 to 16%. The porosity can be measured by the method described in the section [Examples] below.
[0064] According to the research of the present inventor, it was found that a conductor containing silver and glass frit has many voids (vacancies) in the conductor when it is not polished. It is believed that the voids in the conductor become a source of stress concentration, which leads to a decrease in the breaking strength after terminal attachment.
[0065] In addition, according to the present inventor's research, it was found that when a conductor containing silver and glass frit is not polished, the glass frit component is present in a large amount on the surface of the conductor. In particular, when a conductor is formed on a light-shielding layer, it was found that the glass frit component is present in a larger amount on the surface of the conductor. This is presumably because a part of the glass frit component contained in the conductor-forming material and the light-shielding layer-forming material, which are used as necessary, migrates to the surface side during firing of these materials. Generally, the wettability of lead-free solder to glass frit components is low. If a large amount of glass frit components is present on the surface of a conductor, the bonding strength of the lead-free solder to the conductor decreases, making it difficult to form a solder fillet with a good shape, which is thought to result in a decrease in the fracture strength after terminal attachment.
[0066] According to the research of the present inventor, it has been found that polishing the surface of a conductor can reduce voids (vacant holes) in the conductor, which can be a source of stress concentration. It is presumed that polishing the surface of a conductor reduces the depth of voids present on the surface, and furthermore, the silver is stretched, thereby filling the voids present on the surface and surface layer of the conductor. It was also found that polishing the surface of the conductor can reduce the amount of glass frit components present on the surface of the conductor. It is presumed that polishing the surface of the conductor removes the glass frit components that are present in large amounts on the surface. Since the amount of glass frit components present on the surface of the conductor can be reduced, the wettability of the lead-free solder to the conductor can be improved, the bonding strength of the lead-free solder to the conductor can be improved, and a solder fillet with a good shape can be formed. In a method of polishing the surface of a region including a terminal joint of a conductor, compressive stress can be applied to at least the surface of the terminal joint of the conductor, the porosity of the terminal joint and the amount of glass frit components on the surface of the terminal joint can be reduced, and the breaking strength after terminal attachment can be effectively increased.
[0067] Known glass frits can be used for the conductor and the light-shielding layer. Metal elements that include Na, Al, Si, P, Zn, Ba, and Bi can be used. Generally, glass frits for the conductor and the light-shielding layer contain a relatively large amount of Bi, so the ratio of the components of the glass frit on the surface of the conductor can be indicated by the Bi / Ag mass ratio. A higher Bi / Ag mass ratio indicates a higher ratio of the components of the glass frit. The Bi / Ag mass ratio can be measured by energy dispersive X-ray (EDX) analysis or the like.
[0068] In addition, when a conductor is formed on a light-shielding layer, as described above, a part of the glass frit component contained in the material for forming the light-shielding layer may migrate into the conductor during the manufacturing process, and therefore, the glass frit component contained in the conductor before the process of plastically deforming at least the surface of the terminal joint portion by surface polishing or the like may contain a part of the glass frit component that was contained in the material for forming the light-shielding layer.
[0069] One index of the surface polishing level is the ratio of the arithmetic mean surface roughness (Ra) after polishing to that before polishing. When a conductor includes a non-polished portion, this parameter is synonymous with the ratio of the arithmetic mean surface roughness (Ra) of the polished portion to that of the non-polished portion. The ratio of the arithmetic mean surface roughness (Ra) after polishing to that before polishing (=the ratio of the arithmetic mean surface roughness (Ra) of the polished portion to that of the non-polished portion) is not particularly limited, and is preferably 5 to 80%, more preferably 5 to 50%, and particularly preferably 5 to 20%, since this effectively increases the breaking strength after terminal attachment. The surface roughness (Ra) can be measured by the method described in the Examples section below.
[0070] Another indicator of the level of surface polishing is the film thickness reduction rate after polishing relative to before polishing. When a conductor includes a non-polished portion, this parameter is synonymous with the film thickness reduction rate of the polished portion relative to the non-polished portion. The film thickness reduction rate of the polished portion relative to the non-polished portion (=the film thickness reduction rate of the polished portion relative to the non-polished portion) is not particularly limited, and is preferably 4 to 40%, more preferably 4 to 20%, and particularly preferably 4 to 10%, since this effectively increases the breaking strength after terminal attachment. The film thickness reduction rate can be measured by the method described in the section [Examples] below.
[0071] The manufacturing method of the vehicle windshield of the present disclosure is not particularly limited. The method for manufacturing a vehicle windshield according to the present disclosure includes, for example, A step (S2) of applying a silver-containing paste containing silver and glass frit, which are conductive materials, onto a glass plate, which is a material for a glass plate with terminals; A step (S3) of firing the glass plate coated with the conductor material to form a conductor including a terminal joint; A step (S5) of plastically deforming at least a surface of a region including a terminal joint portion of the conductor; The method can include a step (S6) of joining a terminal via lead-free solder onto the terminal joining portion, at least the surface of which has been plastically deformed.
[0072] In the manufacturing method of the vehicle windshield of the present disclosure, compressive stress can be applied to at least the surface of the terminal joint of the conductor in step (S5), and the breaking strength after the terminal is attached can be increased. The stress value of the terminal joint of the conductor after step (S5) may be a negative value, and is preferably -20 MPa or less. The upper limit is more preferably -25 MPa, and particularly preferably -30 MPa. The lower limit is not particularly limited, and is, for example, -50 MPa or -45 MPa.
[0073] The step (S5) may be a step of polishing the surface of the region including the terminal joint of the conductor. In the method of polishing the surface of the region including the terminal joint of the conductor, compressive stress can be applied to at least the surface of the terminal joint of the conductor, the porosity of the terminal joint and the amount of glass frit components on the surface of the terminal joint can be reduced, and the breaking strength after terminal attachment can be effectively increased.
[0074] The surface of the conductor can be polished by a known method, and may be a manual method or an electric method. The manual method includes a method of rubbing the surface of the conductor using an abrasive member such as a metal fiber or an abrasive eraser. The electric method includes a method of polishing the surface of the conductor using an electric cutting tool (also called a hand grinder).
[0075] Examples of metal fibers include steel wool. Metal fibers are available in several sizes depending on the average fiber diameter. In the method using metal fibers, the size and amount of metal fibers used, the rubbing force, the number of times of rubbing, the rubbing time, etc. can be adjusted to adjust at least the surface plastic deformation level, the stress value after polishing, and the surface roughness, etc., in the polished part of the conductor.
[0076] Abrasive erasers contain abrasives (also called abrasive grains) such as alumina and silica, and rubber, and are commercially available under names such as sand erasers and rust erasers. There are several grits depending on the average particle size of the abrasives (abrasive grains) contained. By adjusting the grit size of the abrasive eraser, the rubbing force, the number of rubs, and the rubbing time, it is possible to adjust at least the surface plastic deformation level, the stress value after polishing, and the surface roughness, etc., of the polished part of the conductor.
[0077] Commercially available electric cutting tools (hand grinders) include "Luuter (registered trademark)" manufactured by Nippon Seimitsu Kikai Kogyo Co., Ltd. Electric cutting tools can be used with abrasive tip tools attached. As tip tools, angle tools are preferred from the viewpoint of workability. Examples include angle tools that have an attachment surface for an abrasive disc and are made of a combination of a rubber pad attached to an electric cutting tool and an abrasive disc attached thereto, and ceramic angle tools (also called ceramic angle grindstones) that contain ceramic as an abrasive (abrasive grain), a binder, and an elastic body. Abrasive discs include discs that contain abrasive (abrasive grain) and discs that do not contain abrasive, and when using discs that do not contain abrasive, it is necessary to use an abrasive in combination. Abrasive discs include sandpaper discs, felt discs that do not contain abrasives, felt discs that contain abrasives, and nylon nonwoven discs that contain abrasives (also called cushion discs). Discs that contain abrasives and ceramic angle tools come in several sizes depending on the average particle size of the abrasive (abrasive grain). By adjusting the type and grit size of the tool tip used, the rotation speed, the polishing time, etc., it is possible to adjust at least the surface plastic deformation level, the stress value after polishing, and the surface roughness, etc., of the polished portion of the conductor.
[0078] Generally, for the same material, the smaller the grit size, the larger the average size of the abrasive (abrasive grains) contained, and the greater the abrasive power. In any polishing method, the polishing conditions are adjusted so as not to damage the glass plate and the light-shielding layer (if necessary) and so as not to cause too much abrasive power.
[0079] In an embodiment in which the glass plate with terminals has a light-shielding layer between the glass plate and the terminal joint of the conductor, the method may include a step (S1) of coating a ceramic paste containing a black pigment and glass frit, which are materials for the light-shielding layer, on the glass plate, which is the material for the glass plate with terminals, prior to the step (S2). In this case, the material for the light-shielding layer can be fired in the step (S3) to form the light-shielding layer.
[0080] In the laminated glass, the glass sheet with terminals has an exposed portion that is not covered by the opposing glass sheet via an interlayer film, the conductor is formed on the interlayer film side of the glass sheet with terminals, and a terminal joining portion of the conductor can be formed in the exposed portion of the glass sheet with terminals. In this embodiment, a step (S4) of laminating a plurality of glass plates via an interlayer film can be included between the steps (S3) and (S5).
[0081] In the laminated glass, the conductor can be formed on the side of the glass sheet with terminals opposite the interlayer film side. Even in this embodiment, a step (S4) of laminating a plurality of glass plates via an interlayer film can be included between the steps (S3) and (S5).
[0082] [First embodiment] The structure of a vehicle windshield according to a first embodiment of the present disclosure will be described with reference to the drawings. Fig. 1 is an overall plan view of a vehicle windshield of this embodiment. Fig. 2 is a partially enlarged plan view of Fig. 1. Figs. 1 and 2 are views before terminal joining. Figs. 1 and 2 are both perspective views, with the front side of the figure being the inside of the vehicle and the back side being the outside of the vehicle. Fig. 3 is a cross-sectional view taken along line III-III in Fig. 2. In Fig. 3, the upper side is the outside of the vehicle and the lower side is the inside of the vehicle. These figures are all schematic views, and for ease of viewing, the scale of each component in each drawing is appropriately different from the actual one.
[0083] The planar shape of the vehicle windshield 1 can be designed as appropriate, and may be, for example, a generally curved shape of a plate having a generally trapezoidal shape in plan view as shown in FIG. As shown in FIG. 3, the vehicle windshield 1 of this embodiment includes a laminated glass 10 in which an outer glass sheet 11 (a glass sheet on the outer side of the vehicle) and an inner glass sheet 13 (a glass sheet on the inner side of the vehicle) are bonded together with an intermediate film 12 interposed therebetween. In this embodiment, the laminated glass 10 includes an outer glass sheet 11, a terminal-equipped glass sheet 11X formed on the vehicle inner surface (the surface on the interlayer 12 side) S2 of the outer glass sheet 11 and made of a material containing silver and glass frit, the conductor 20 having a terminal joint 20T to which a terminal 102 is joined, and the terminal 102 joined via lead-free solder 101 onto the terminal joint 20T of the conductor 20. The laminated glass may be made by bonding three or more glass sheets together.
[0084] 1, the vehicle windshield 1 of this embodiment has one or more light-shielding layers BL in its peripheral region. The number of light-shielding layers BL, the glass surface on which the light-shielding layers BL are formed, and the region in which the light-shielding layers BL are formed can be designed appropriately. 3, in this embodiment, a light-shielding layer BL2 is formed in the peripheral region of the vehicle interior surface S2 of the outer glass sheet 11, and a conductor 20 including an electrical function portion is formed on this light-shielding layer BL2. Note that, in the present disclosure, since an effect of improving the breaking strength of the glass sheet with terminals 11X is obtained, the glass sheet with terminals 11X can have the light-shielding layer BL2 between the outer glass sheet 11 and the terminal joint portion 20T. 3, a light-shielding layer BL4 may be formed in a peripheral region of at least one surface of the inner glass sheet 13. In the illustrated example, the light-shielding layer BL4 is formed in a peripheral region of the vehicle inner surface S4 of the inner glass sheet 13.
[0085] In this embodiment, the conductor 20 has a function of melting frost, snow, ice, etc. adhering to the wiper, thereby preventing the wiper from freezing. In Fig. 1, the area indicated by the dashed line and marked with the symbol WP is the movable area of the wiper. As shown in Figs. 1 and 2, the conductor 20 includes an electrical functional part consisting of one or more heating wires 20L or heating layers. Here, an example is illustrated in which the conductor 20 includes a plurality of heating wires 20L. The conductor 20 may further include a power supply part including a pair of power supply electrodes (a pair of bus bars) 20B. One of the pair of power supply electrodes (a pair of bus bars) 20B is a positive electrode and the other is a negative electrode. The conductor 20 may be formed, for example, at the lower end and / or at least one side end of the vehicle windshield 1. The configuration, pattern and formation area of the conductor 20 may be designed as appropriate.
[0086] 2 and 3, the inner glass plate 13 has a notch 13N at a lower end portion, whereby the terminal-equipped glass plate 11X has an exposed portion 11E that is not covered by the inner glass plate 13 that faces the terminal-equipped glass plate 11X via the interlayer 12. In this embodiment, the conductor 20 is formed on the interlayer 12 side of the terminal-equipped glass plate 11X. At least a portion of each of the pair of power supply electrodes (pair of bus bars) 20B is formed in the exposed portion 11E of the terminal-equipped glass plate 11X and is exposed and not covered by the inner glass plate 13.
[0087] 2, in each of the pair of power supply electrodes (pair of bus bars) 20B, the exposed portion 20E of the power supply electrode 20B includes a terminal joint portion 20T, and a terminal 102 is joined onto the terminal joint portion 20T via lead-free solder 101. A power supply member 103 made of a round wire or foil-shaped conductor is fixed to the terminal 102. See also FIG. 5B for the exposed portion 20E. The terminal joint 20T of the conductor 20 is the portion directly below the lead-free solder 101. In the drawing, the formation region of the terminal joint 20T is the region between two dashed lines T1 and T2. The position of the terminal joint 20T of the conductor 20 is not clearly determined from the beginning. In the power supply electrode 20B, the portion directly below the lead-free solder 101 after the terminal 102 is joined via the lead-free solder 101 is the terminal joint 20T.
[0088] Fig. 4 is a partially enlarged cross-sectional view of the cross section of the laminated structure of the terminal 102 / lead-free solder 101 / power supply electrode 20B including the terminal joint 20T / light-shielding layer BL2 / outer glass plate 11 shown in Fig. 3, as viewed from the left side of Fig. 3. Here, the laminated structure is upside down for ease of visualization. The power supply member 103 is preferably a round or foil-shaped conductor, more preferably a round or foil-shaped coated conductor, and more preferably a wire harness, flat harness, or the like. The tip of the power supply member 103 is an exposed conductor portion, and the terminal 102 is fixed to this exposed conductor portion. A known crimp terminal is preferable as the terminal 102. The crimp terminal preferably has a power supply member joint 102A (see FIG. 3) that contacts the tip end (exposed conductor portion) of the power supply member 103, and a solder joint 102B (see FIGS. 3 and 4) that contacts the lead-free solder 101.
[0089] When a wire harness is used as the power supply member 103, the crimp terminal is preferably a crimp terminal consisting of a power supply member joint 102A that crimps and fixes the tip end (exposed conductor portion) of the wire harness, and a bridge-shaped portion having solder joints 102B at both ends, as shown in Figures 3 and 4. The crimp terminal may not have a bridge-shaped portion and may have one solder joint 102B.
[0090] The terminal 102 is preferably a metal terminal. The metal constituting the terminal is not particularly limited, and examples thereof include metals such as Cu, Fe, Cr, Ni, and Zn; alloys containing one or more metal elements such as Cu, Fe, Cr, Ni, and Zn; and combinations thereof. Examples of alloys include stainless steel (SUS) and brass. The surface of the terminal 102 may be subjected to a surface treatment such as tin plating. At least a part of the terminal 102 may be covered with an insulating material. The thickness of the terminal 102 is not particularly limited, and is preferably 0.4 to 0.8 mm. The terminal 102 made of a single material can be manufactured, for example, by punching a metal plate (press processing using a punching die) to obtain a metal plate of a desired size, and bending the metal plate. For example, a terminal 102 (preferably a crimp terminal) is fixed by crimping to a tip portion (exposed conductor portion) of the power supply member 103, and the terminal 102 is joined to a terminal joint portion 20T in the power supply electrode 20B via lead-free solder 101. The tip portion (exposed conductor portion) of the power supply member 103 and the terminal 102 may be connected by soldering or by welding.
[0091] In this embodiment, at least a region of the exposed portion 20E of each power supply electrode 20B including the terminal joint portion 20T is a compressive stress portion 20CS in which at least the surface is subjected to compressive stress. In this embodiment, the entire region of the exposed portion 20E of each power supply electrode 20B, which includes at least the terminal joint portion 20T, may be a compressive stress portion 20CS. The compressive stress portion 20CS was measured using a micro X-ray stress measuring device. 2 The stress value measured by the ψ method may be a negative value, and is preferably -20 MPa or less. The upper limit is more preferably -25 MPa, and particularly preferably -30 MPa. The lower limit is not particularly limited, and is, for example, -50 MPa or -45 MPa.
[0092] In this embodiment, the exposed portion 20E of each power supply electrode 20B may be a polished portion 20P having a polished surface, at least in an area including the terminal joint portion 20T. In the example shown in Fig. 2, in each power supply electrode 20B, the entire exposed portion 20E is the polished portion 20P having a polished surface (i.e., the exposed portion 20E and the polished portion 20P are coincident), and the other portion (non-exposed portion) is the non-polished portion 20NP having an unpolished surface. The area of the polished portion 20P may be narrower than the area of the exposed portion 20E.
[0093] The porosity of the polishing portion 20P of the conductor 20 is preferably 10% or less, more preferably 8% or less, particularly preferably 7% or less, and particularly preferably 3% or less. The lower limit of the porosity of the polishing portion 20P of the conductor 20 is, for example, 0.5%. The porosity of the non-polished portion 20NP of the conductor 20 is greater than the porosity of the polished portion 20P and may be greater than 10% or less than 10%, for example, 15 to 16%.
[0094] In order to effectively increase the breaking strength after terminal attachment, the ratio of the arithmetic mean surface roughness (Ra) of the polished portion 20P to the non-polished portion 20NP of the conductor 20 is preferably 5 to 80%, more preferably 5 to 50%, and particularly preferably 5 to 20%. Since the breakdown strength after terminal attachment can be effectively increased, the film thickness reduction rate of the polished portion 20P relative to the non-polished portion 20NP of the conductor 20 is preferably 4 to 40%, more preferably 4 to 20%, and particularly preferably 4 to 10%.
[0095] (Manufacturing method) An example of a method for manufacturing a vehicle windshield according to this embodiment will be described with reference to the drawings, in which: Figures 5A to 5D are schematic cross-sectional views corresponding to Figure 3.
[0096] (Process (S1)) First, if necessary, a ceramic paste containing black pigment and glass frit, which are materials for the light-shielding layer BL2, is applied to a specified area on the vehicle interior surface S2 of the outer glass sheet 11 (the glass sheet on the outside of the vehicle), and dried to form a ceramic paste layer. Furthermore, if necessary, a ceramic paste containing a black pigment and glass frit, which are materials for the light-shielding layer BL4, is applied to a specified area on the vehicle interior surface S4 of the inner glass sheet 13 and dried to form a ceramic paste layer. The drying conditions for the ceramic paste can be appropriately designed depending on the paste composition, and for example, a temperature of 120 to 150° C. and about 5 minutes are preferable. The inner glass plate 13 is preliminarily processed into a shape having a notch 13N.
[0097] (Process (S2)) Next, a silver-containing paste containing silver and glass frit, which are materials for the conductor 20, is applied directly onto the vehicle inner surface S2 of the outer glass sheet 11, or onto the ceramic paste layer formed as necessary on the outer glass sheet 11, and then dried to form a conductive paste layer. The drying conditions for the silver-containing paste can be appropriately designed depending on the paste composition, and for example, drying at 120 to 150°C for about 5 minutes is preferable.
[0098] (Process (S3)) Next, the outer glass sheet 11 and the inner glass sheet 13 after the above steps are heated simultaneously or individually to a temperature equal to or higher than the softening point (for example, 600 to 700°C) to bend each glass sheet. In this step, the ceramic paste layer and the silver-containing paste layer formed as required are fired, and one or more light-shielding layers BL and conductors 20 are formed as required. After firing, each glass sheet is slowly cooled. After the above steps, as shown in Figure 5A, a conductor-attached glass plate 11Y is obtained which, if necessary, has a light-shielding layer BL2 on one surface of the outer glass plate 11 and has a conductor 20 formed directly on the outer glass plate 11 or on the light-shielding layer BL2, and an inner glass plate 13 which may have a light-shielding layer BL4.
[0099] (Process (S4)) Next, as shown in Fig. 5A, the conductor-attached glass sheet 11Y and the inner glass sheet 13 are bonded together via a resin film 12F that is the material of the interlayer 12. After this step, a laminated glass 10 is obtained as shown in Fig. 5B.
[0100] The resin constituting the resin film 12F is not particularly limited, and is preferably one or more resins selected from the group consisting of polyvinyl butyral (PVB), ethylene vinyl acetate copolymer (EVA), cycloolefin polymer (COP), polyurethane (PU), and ionomer resin. The resin film 12F may contain one or more additives other than resins as necessary. Examples of additives include colorants such as pigments. The resin film 12F may be colorless and transparent or colored and transparent. The resin film 12F may have a single layer structure or a laminate structure of two or more layers.
[0101] The lamination can be performed by thermocompression bonding. Examples of the thermocompression bonding method include a method in which a provisional laminate obtained by overlapping a plurality of members as shown in Fig. 5A is placed in a bag made of rubber or the like and heated in a vacuum; a method in which the provisional laminate is pressurized and heated using an automatic pressurized heat treatment device, an autoclave, or the like; and a combination of these. The thermocompression bonding conditions of temperature, pressure and time are not particularly limited and are designed according to the type and temperature of the resin film 12F. The thermocompression bonding conditions may be such that the resin film 12F is softened and sufficiently pressurized, and the conductor-attached glass plate 11Y and the inner glass plate 13 which may have a light-shielding layer BL4 are sufficiently bonded via the resin. Thermocompression bonding may be performed in multiple stages by changing the method or conditions. The constituent resin of the resin film 12F softens and spreads so as to fill the space between the conductor-attached glass plate 11Y and the inner glass plate 13 which may have a light-shielding layer BL4.
[0102] (Process (S5)) Next, at least the surface of the region including the terminal joint portion 20T of the conductor 20 is plastically deformed. Step (S5) can be, for example, a step of polishing the surface of the region including the terminal joint portion 20T of the conductor 20. In this embodiment, the surface of the region including the terminal joint portion 20T in the exposed portion 20E of each power supply electrode 20B can be polished. The entire exposed portion 20E may be surface-polished, or only a part of the exposed portion 20E may be surface-polished. Generally, the stress remaining in conductor 20 before step (S5) is performed is tensile stress, and the stress value of conductor 20 before step (S5) is performed is a positive value. At least the surface of terminal joint 20T can be plastically deformed by a method such as surface polishing to make at least the surface of terminal joint 20T into compressive stress portion 20CS in which compressive stress is applied. The stress value of compressive stress portion 20CS is a negative value, preferably -20 MPa or less. After this step, a laminated glass 10 can be obtained that has a conductor 20 in which at least the surface of the terminal joint portion 20T is a compressive stress portion 20CS, as shown in Fig. 5C. The conductor 20 is composed of a polished portion 20P and a non-polished portion 20NP, and at least the surface of the polished portion 20P can be a compressive stress portion 20CS. In the conductor 20, the film thickness of the polished portion 20P becomes thinner than the film thickness of the non-polished portion 20NP due to polishing.
[0103] (Process (S6)) Next, as shown in Fig. 5D, terminals 102 are joined onto terminal joints 20T included in exposed portions 20E of each power supply electrode 20B via lead-free solder 101. Power supply members 103, preferably made of round or foil-shaped conductive wires, are fixed (preferably by crimping) to terminals 102 in advance by a known method. For details of solder joints, please also refer to Fig. 4.
[0104] Soldering can be performed by known methods, preferably using a soldering iron or resistance heating. When using a soldering iron, the bonding can be performed, for example, as follows. An appropriate amount (e.g., 0.05 to 0.10 g) of lead-free solder is applied to each solder joint of the terminal. This terminal is then placed on the terminal joint of the conductor whose surface has been polished. In this state, the tip of a soldering iron set to a temperature equal to or higher than the melting point of the lead-free solder is pressed against the solder joint of the terminal to heat and melt the lead-free solder. The soldering iron is then removed from the terminal, and the lead-free solder is allowed to solidify by natural cooling. It is recommended to apply flux to the surface of the unmelted lead-free solder and / or the surface of the solder joint of the terminal before soldering. The flux melts the metal oxide film, resulting in a good joint. It is recommended to place an appropriate amount of lead-free solder on the tip of the soldering iron and heat it to melt it before soldering. This solder is called pre-solder and can increase the thermal conductivity during soldering.
[0105] Generally, to bond a conductor and solder well, it is necessary to form an alloy layer at the bonding interface between the conductor and the solder, which contains an alloy of one or more metal elements contained in the conductor and multiple metal elements contained in the solder. For this reason, the solder is heated to its melting point or higher to perform solder bonding. The melting point of lead-free solder such as SnAg-based and SnAgCu-based solder is, for example, about 220°C. In this case, the solder bonding temperature is preferably, for example, about 300°C. If necessary, the terminals 102 are sealed with a resin such as a silicone resin by a known method. In the manner described above, the vehicle windshield 1 of the present embodiment is manufactured.
[0106] The manufacturing method of the vehicle windshield 1 of this embodiment includes a step (S5) of plastically deforming at least the surface of a region including the terminal joint portion 20T of the conductor 20 by surface polishing or the like, and a step (S6) of joining the terminal 102 via the lead-free solder 101 onto the terminal joint portion 20T whose surface has been plastically deformed at least. In this method, in the step (S5), a compressive stress can be applied to at least the surface of the terminal joint portion 20T of the conductor 20, and the breaking strength after the terminal is attached can be increased. The method of polishing the surface of the region including the terminal joint 20T of the conductor 20 can impart compressive stress to at least the surface of the terminal joint 20T of the conductor 20, thereby reducing the porosity of the terminal joint 20T and the amount of glass frit components on the surface of the terminal joint 20T, and effectively increasing the breaking strength after terminal attachment.
[0107] [Design modification example of the first embodiment] In the first embodiment, the conductor 20 includes an electrical function part made of one or more heating wires 20L or heating layers, and a power supply part including a pair of power supply electrodes (a pair of bus bars) 20B. The conductor 20 may include only a power supply part without including an electrical function part, and the power supply part may be connected to an electrical function part not included in the conductor 20.
[0108] For example, as shown in Fig. 6, a conductor 40 including an electrical function part can be formed on a resin film 12F, which is the material of the intermediate film 12. For example, the conductor 40 can include an electrical function part consisting of one or more heating wires or layers, and can further include a power supply part including a pair of power supply electrodes (a pair of bus bars) as necessary. In Fig. 6, the same components as those in the first embodiment are given the same reference symbols, and descriptions thereof will be omitted. For example, one or more metal wires (e.g., tungsten wires, etc.) as one or more heating wires, and a pair of metal foils (e.g., copper foils, etc.) as a pair of power supply electrodes (bus bars) as needed, can be arranged on the resin film 12F. Alternatively, a resin film (e.g., a polyethylene terephthalate (PET) film) having one or more heating wires and a pair of power supply electrodes formed on its surface may be arranged on the resin film 12F.
[0109] The electrical function part formed on the resin film 12F is connected to the conductor 20 consisting only of a power supply part included in the conductor-attached glass sheet 11Y after the conductor-attached glass sheet 11Y and the inner glass sheet 13 are bonded together via the intermediate film 12. The electrical function part formed on the resin film 12F may be connected to the conductor 20 consisting only of a power supply part included in the conductor-attached glass sheet 11Y via the power supply part formed on the resin film 12F. The configuration, material, forming method, pattern and forming area of the conductor 40 formed on the resin film 12F, which includes an electrical functional part and, if necessary, a power supply part, and the conductor 20 consisting only of a power supply part included in the conductor-attached glass plate 11Y, can be designed appropriately.
[0110] In this design modification example, as shown in FIG. 6, a conductor-attached glass plate 11Y and an inner glass plate 13 are bonded together via an intermediate film 12 to produce laminated glass, and then, as in the first embodiment, a process (S5) of plastically deforming at least the surface of an area including the terminal joint 20T of each power supply electrode 20B, and a process (S6) of joining a terminal 102 via lead-free solder 101 to the terminal joint 20T of each power supply electrode 20B whose at least the surface has been plastically deformed can be carried out.
[0111] [Second embodiment] The structure of a vehicle windshield according to a second embodiment of the present invention will be described with reference to the drawings. FIG. 7A is an overall plan view of the vehicle windshield according to this embodiment. FIG. 7B is a partially enlarged plan view of FIG. 7A. FIGS. 7A and 7B are views before terminal bonding. FIG. 8 is a cross-sectional view taken along line VIII-VIII of FIG. 7B. In these figures, the plan view and the partially enlarged plan view are both perspective views. These figures are all schematic views, and in order to make them easier to see, the scale of each component is appropriately changed from the actual one in each drawing. The same reference symbols are used for the same components as those in the first embodiment, and their description will be omitted.
[0112] As shown in FIG. 8, the vehicle windshield 2 of this embodiment includes a laminated glass 50 in which an outer glass sheet 11 (a glass sheet on the outer side of the vehicle) and an inner glass sheet 13 (a glass sheet on the inner side of the vehicle) are bonded together with an intermediate film 12 interposed therebetween. In this embodiment, the laminated glass 50 includes an inner glass sheet 13, a terminal-equipped glass sheet 13X formed on the vehicle inner surface S4 (the surface opposite to the interlayer 12 side) of the inner glass sheet 13 and made of a material containing silver and glass frit, the conductor 80 having a terminal joint 80T to which a terminal 102 is joined, and the terminal 102 joined via lead-free solder 101 onto the terminal joint 80T of the conductor 80. The laminated glass may be made by bonding three or more glass sheets together.
[0113] As shown in FIG. 7A, the vehicle windshield 2 has an optical device mounting area OP in which an optical device is mounted, and a light-transmitting portion TP located within the optical device mounting area OP through which incident light from the outside to the optical device and / or emitted light from the optical device passes. As shown in the figure, the light-transmitting portion TP can be formed in a region relatively close to one end side 50E of the vehicle windshield 2 (the upper end side in the illustrated example).
[0114] The optical device may include, for example, optical instruments such as ADAS (Advanced Driver Assistance systems) cameras, LiDAR (Light Detection And Ranging), radar, and optical sensors that acquire information in front of the vehicle for the purposes of autonomous driving and preventing collision accidents, and a housing called a bracket or the like that houses these instruments. The shapes of the optical device mounting area OP and the light-transmitting part TP can be appropriately designed according to the shape of the optical device, and examples of such shapes include a substantially trapezoidal shape and a substantially rectangular shape. The shapes of the optical device mounting area OP and the light-transmitting part TP may be similar or non-similar. In the illustrated example, the shapes of the optical device mounting area OP and the light-transmitting part TP are substantially trapezoidal.
[0115] As in the first embodiment, as shown in Fig. 7A, the vehicle windshield 2 of this embodiment can have one or more light-shielding layers BL in the region including the peripheral region. The light-shielding layer BL can include a black pigment and a glass frit. The number of light-shielding layers BL, the glass surface on which the light-shielding layer BL is formed, and the region in which the light-shielding layer BL is formed can be designed appropriately.
[0116] In this embodiment, as shown in Figure 8, a light-shielding layer BL4 is formed in a specified area on the vehicle interior surface S4 (the surface opposite the intermediate film 12) of the inner glass plate 13, and most of the conductor 80 is formed on this light-shielding layer BL4. As shown in FIG. 7A, the formation area of the light-shielding layer BL4 can include the area excluding the light-transmitting portion TP from the optical device mounting area OP, the area surrounding the optical device mounting area OP, and the peripheral area of the vehicle windshield 2. In the illustrated example, the formation area of the light-shielding layer BL4 includes the area excluding the light-transmitting portion TP from the optical device mounting area OP and the area surrounding the optical device mounting area OP, as well as an area R41 excluding the light-transmitting portion TP from a substantially trapezoidal area defined by one end edge 50E (the upper end edge in the illustrated example) of the laminated glass 50 and edges B41 to B43, and a peripheral area R42 of the vehicle windshield 2. In the illustrated example, the light-shielding layer BL4 surrounds all four sides of the light-transmitting portion TP, but it is sufficient that the light-shielding layer BL4 surrounds at least a portion of the light-transmitting portion TP, and for example, it may surround only three sides of the light-transmitting portion TP, which has an approximately trapezoidal or approximately rectangular shape. The wavelength range of light transmitted through the light-transmitting portion TP is not particularly limited, and may be, for example, the visible light range, the infrared light range, or a range from the visible light range to the infrared light range.
[0117] 8, if necessary, a light-shielding layer BL2 can be formed on the vehicle inner surface S2 of the outer glass sheet 11. The formation region of the light-shielding layer BL2 can include, for example, the region excluding the light-transmitting part TP from the optical device mounting region OP, the region around the optical device mounting region OP, and the peripheral region of the vehicle windshield 2, similar to the light-shielding layer BL4. The planar shape of the region where the light-shielding layer BL2 is formed and the planar shape of the region where the light-shielding layer BL4 is formed can be designed independently of each other, and the planar shapes of these regions may be the same or different.
[0118] As shown in Fig. 7B, in this embodiment, the conductor 80 includes an electrical function section consisting of one heating wire 80L or heating layer. The conductor 80 further includes a power supply section consisting of a pair of power supply electrodes (a pair of bus bars) 80B. The conductor 80 may include multiple heating wires 80L. The configuration and pattern of the conductor 80 can be designed as appropriate. The electrical conductors 80 are preferably located within the optical device mounting area OP. The conductor 80 may be formed on almost the entire surface of the vehicle windshield 2 .
[0119] The sensing accuracy of the optical device can be improved by providing an electric heating wire 80L or an electric heating layer for preventing fogging and frost in an area including a translucent portion TP located in front of optical equipment such as a camera and radar included in the optical device. The line pattern and arrangement pattern of the heating wire 80L are not particularly limited. For example, as shown in Fig. 7B, when viewed from above, the heating wire 80L is folded back so as to cross the light-transmitting portion TP multiple times, which is preferable because it can efficiently remove frost and water droplets adhering to the light-transmitting portion TP. The width of the heating wire 80L may change on the way from one power supply electrode to the other power supply electrode. In order to adjust the amount of heat generated by the heating wire 80L, the heating wire 80L may be disposed in an area other than the light-transmitting part TP.
[0120] As shown in FIG. 8, in this embodiment, the conductor 80 is formed on the vehicle interior surface S4 of the inner glass sheet 13. As in the first embodiment, each of the pair of power supply electrodes (pair of bus bars) 80B includes a terminal joint portion 80T, and a terminal 102 is joined onto the terminal joint portion 80T of the conductor 80 via lead-free solder 101. A power supply member 103 made of a round wire or foil-shaped conductor is fixed to the terminal 102. As in the first embodiment, the terminal joint 80T of the conductor 80 is a portion directly below the lead-free solder 101. In the drawing, the area of the terminal joint 80T is an area sandwiched between two dashed lines T1 and T2. Note that the position of the terminal joint 80T of the conductor 80 is not clearly determined from the beginning. In the power supply electrode 80B, the portion directly below the lead-free solder 101 after the terminal 102 is joined via the lead-free solder 101 is the terminal joint 80T. In this embodiment, the light-shielding layer BL is not formed in the light-transmitting portion TP.
[0121] In this embodiment, at least a region including the terminal joint portion 80T of each power supply electrode 80B is a compressive stress portion 80CS in which at least the surface is subjected to compressive stress. In this embodiment, a region of each power supply electrode 80B including at least the terminal joint portion 80T can be a compressive stress portion 80CS in its entirety. The compressive stress portion 80CS was measured using a micro X-ray stress measuring device. 2 The stress value measured by the ψ method may be a negative value, and is preferably -20 MPa or less. The upper limit is more preferably -25 MPa, and particularly preferably -30 MPa. The lower limit is not particularly limited, and is, for example, -50 MPa or -45 MPa.
[0122] In this embodiment, the area of each power supply electrode 80B including at least the terminal joint portion 80T can be a ground portion 80P having a ground surface. In the example shown in Fig. 7B and Fig. 8, the entire power supply electrode 80B is a ground portion 80P having a ground surface (i.e., the power supply electrode 80B and the ground portion 80P are coincident), and the remaining portion, the heating wire 80L, is a non-ground portion 80NP having an unground surface. The area of the ground portion 80P may be narrower than the area of the power supply electrode 80B.
[0123] The polishing portion 80P of the conductor 80 preferably has a porosity of 10% or less, more preferably 8% or less, particularly preferably 7% or less, and particularly preferably 3% or less. The lower limit of the porosity of the polishing portion 80P of the conductor 80 is, for example, 0.5%. The porosity of the non-polished portion 80NP of the conductor 80 is greater than the porosity of the polished portion 80P and may be greater than 10% or less than 10%, for example, 15 to 16%.
[0124] Since this effectively increases the breaking strength after terminal attachment, the ratio of the arithmetic mean surface roughness (Ra) of the polished portion 80P to the non-polished portion 80NP of the conductor 80 is preferably 5 to 80%, more preferably 5 to 50%, and particularly preferably 5 to 20%. Since the breakdown strength after terminal attachment can be effectively increased, the film thickness reduction rate of the polished portion 80P of the conductor 80 relative to the non-polished portion 80NP is preferably 4 to 40%, more preferably 4 to 20%, and particularly preferably 4 to 10%.
[0125] (Manufacturing method) Each step of the method for manufacturing a vehicle windshield according to this embodiment will be described with reference to the drawings. 9A to 9C are schematic cross-sectional views corresponding to FIG. (Process (S1)) First, as in the first embodiment, a ceramic paste containing black pigment and glass frit, which are materials for the light-shielding layer BL4, is applied, as necessary, to a specified area on the interior surface S4 of the inner glass sheet 13 (the glass sheet on the inside of the vehicle), and dried to form a ceramic paste layer. Furthermore, if necessary, a ceramic paste containing a black pigment and glass frit, which are materials for the light-shielding layer BL2, is applied to a specified area on the vehicle interior surface S2 of the exterior glass sheet 11, and then dried to form a ceramic paste layer. The drying conditions for the ceramic paste layer are the same as those in the first embodiment.
[0126] (Process (S2)) As in the first embodiment, a silver-containing paste containing silver powder and glass frit is applied directly onto the vehicle inner surface S4 of the inner glass sheet 13, or onto a ceramic paste layer formed as necessary on the vehicle inner surface S4 of the inner glass sheet 13, and then dried to form a silver-containing paste layer. The drying conditions for the conductive paste layer are the same as in the first embodiment.
[0127] (Process (S3)) Next, similarly to the first embodiment, the outer glass sheet 11 and the inner glass sheet 13 after the above process are heated to a temperature equal to or higher than the softening point, and each glass sheet is bent. In this process, the ceramic paste layer and the silver-containing paste layer formed as required are fired, and one or more light-shielding layers BL and conductors 80 are formed as required. After firing, each glass sheet is slowly cooled. The firing temperature is the same as in the first embodiment. After the above steps, an outer glass plate 11 which may have a light-shielding layer BL2 and a conductor-attached glass plate 13Y having a light-shielding layer BL4, if necessary, on one surface S4 of the inner glass plate 13 and a conductor 80 formed directly on the inner glass plate 13 or on the light-shielding layer BL4 are obtained.
[0128] Next, similarly to the first embodiment, the outer glass plate 11 which may have a light-shielding layer BL2 and the conductor-attached glass plate 13Y are bonded together via the intermediate film 12 by a known method. After these steps, a laminated glass 50 shown in Fig. 9A is obtained.
[0129] (Process (S5)) Next, at least the surface of the region including the terminal joint portion 80T of the conductor 80 is plastically deformed. Step (S5) can be, for example, a step of polishing the surface of the region including the terminal joint portion 80T of the conductor 80. The entire surface of each power supply electrode 80B may be polished, or only a portion of each power supply electrode 80B may be polished. Generally, the stress remaining in the conductor 80 before step (S5) is performed is tensile stress, and the stress value of the conductor 80 before step (S5) is performed is a positive value. At least the surface of the terminal joint portion 80T can be plastically deformed by a method such as surface polishing to make at least the surface of the terminal joint portion 80T into a compressive stress portion 80CS in which a compressive stress is applied. The stress value of the compressive stress portion 80CS is a negative value, preferably -20 MPa or less. After this step, it is possible to obtain a laminated glass 50 having a conductor 80 in which at least the surface of the terminal joint portion 80T is a compressive stress portion 80CS, as shown in Fig. 9B. The conductor 80 is composed of a polished portion 80P and a non-polished portion 80NP, and at least the surface of the polished portion 80P can be a compressive stress portion 80CS. In the conductor 80, the film thickness of the polished portion 80P becomes thinner than the film thickness of the non-polished portion 80NP due to polishing.
[0130] (Process (S6)) Next, as in the first embodiment, as shown in Fig. 9C, terminal 102 is joined onto terminal joint portion 80T of polished portion 80P included in each power supply electrode 80B via lead-free solder 101. Power supply member 103, preferably made of a round wire or foil conductor, is fixed (preferably by crimping) to terminal 102 in advance by a known method. For solder joining, please also refer to Fig. 4. In this manner, the vehicle windshield 2 of the present embodiment is manufactured.
[0131] As in the first embodiment, the method for manufacturing the vehicle windshield 2 of this embodiment includes a step (S5) of plastically deforming at least the surface of a region including the terminal joint portion 80T of the conductor 80, and a step (S6) of joining the terminal 102 via the lead-free solder 101 onto the terminal joint portion 80T whose at least the surface has been plastically deformed. In this method, in the step (S5), a compressive stress can be applied to at least the surface of the terminal joint portion 80T of the conductor 80, and the breaking strength after the terminal is attached can be increased. The method of polishing the surface of the region including the terminal joint 80T of the conductor 80 can impart compressive stress to at least the surface of the terminal joint 80T of the conductor 80, thereby reducing the porosity of the terminal joint 80T and the amount of glass frit components on the surface of the terminal joint 80T, and effectively increasing the breaking strength after terminal attachment.
[0132] As described above, the present disclosure can provide a vehicle windshield and a manufacturing method thereof that include a portion in which a conductor and a terminal are joined using lead-free solder and that can increase the breaking strength after the terminals are attached. EXAMPLES
[0133] The present invention will be described below based on examples, but is not limited to these. Examples 12 to 17, 22 to 27, 32 to 35, and 42 to 45 are examples, and Examples 11, 21, 31, and 41 are comparative examples.
[0134] [Evaluation items and evaluation methods] The evaluation items and evaluation methods are as follows. (porosity) A silver-containing paste was applied to the same glass plate as in each example, and the plate was baked and polished under the same conditions as in each example to obtain a glass plate for evaluation with a conductor (Glass plate for evaluation 1, without a light-shielding layer). A sample of a size that would allow easy observation of the terminal junction of the conductor was cut out from this glass plate for evaluation. The terminal joints of the above samples were immersed in epoxy resin ("53 type" manufactured by Aqura Corporation) and cured at room temperature to embed the terminal joints in the resin. The terminal joint of the resin-embedded sample was cut in the thickness direction using a high-speed diamond wheel saw (Precis Co., Ltd.'s "Mecatome T180"). The cut surface of the terminal joint was polished using an automatic polishing device (Precis Co., Ltd.'s "Mecatech 234"). Furthermore, if necessary, ion milling was performed using Hitachi High-Tech's "ArBlade 5000". Using a field emission scanning electron microscope (FE-SEM, Hitachi High-Technologies Corporation, "Regulus8220"), 2500x images were taken at three randomly selected locations on the cut surface of the terminal junction at a voltage of 3 kV. In the cross-sectional SEM image of the conductor, light gray areas corresponding to silver-containing regions, dark gray areas corresponding to glass frit-containing regions, and black areas corresponding to voids were confirmed. The images were processed using a commercially available image analysis software (Mitani Shoji Co., Ltd., "WinRooF2018") to determine the porosity of the conductor as the ratio of the cross-sectional area of the black areas corresponding to voids to the total cross-sectional area of the above three regions. The average porosity of the three cross-sectional SEM images was calculated, and this was used as the porosity (%) data.
[0135] (Thickness reduction) A stylus-type measurement was performed using a surface roughness meter (Tokyo Seimitsu Co., Ltd., "Surfcom NEX 001") to measure the amount of film thickness reduction of the conductor after polishing compared to before polishing. A total of four measurements were performed for each condition, and the average value was used as the data for the amount of film thickness reduction.
[0136] (Surface roughness (Ra)) The arithmetic mean roughness (Ra) of the conductor before and after polishing was measured using a surface roughness meter (Tokyo Seimitsu Co., Ltd. "Surfcom NEX 001"). A total of three measurements were taken for each condition, and the average value was used as the arithmetic mean roughness (Ra) data. The ratio (%) of the arithmetic mean surface roughness (Ra) of the conductor after polishing to that before polishing was then calculated.
[0137] (Stress value of terminal joint) The stress value of the terminal joint of the conductor was measured using Rigaku's "Micro X-ray Stress Measurement System AutoMATE II." The measurement method and conditions were as follows. The diffraction peak position was identified by the half-width midpoint method. ·Measurement method: sin 2 ψ method, parallel inclination method, and constant ψ0 method (also called fixed incidence angle method) X-ray source: CuKα radiation (parallel beam optical system using a 2.0mmφ collimator) X-ray tube voltage and current: 40kV and 40mA Diffraction surface: Ag(222) surface · 2θ of the unstrained Ag(222) surface: 152.1° 2θ measurement range: 142°~162° Angle ψ between the normal to the sample surface and the normal to the diffraction surface: 0.0°, 13.6°, 19.5°, 24.1°, 28.1°, 31.8°, 35.3°, 38.6°, 41.8°, and 45.0° (Note that ψ was oscillated within ±2° to improve measurement accuracy.) Counting time: 30 seconds ·Number of smoothing points: 11 ·LP correction: execution, filter method Filter: V Linear absorption coefficient: 6482.7 cm -1 A total of two measurements were performed for each sample, and the average value was used as the stress value data for the terminal joint.
[0138] (Breaking strength before or after terminal attachment) A ring bending test was carried out in a room temperature (20 to 25°C) environment using an autograph (Shimadzu Corporation "AGS-X", maximum load: 5 kN) in accordance with ASTM-C1499-1. The evaluation glass plate 1 or 2 before or after terminal attachment was placed on a support ring with a diameter of 98 mm, with the surface on which the conductor was formed facing down. A load ring with a diameter of 46 mm was placed on this evaluation glass plate. The central axis of the support ring, the central axis of the glass plate, and the central axis of the load ring were aligned. A load was applied around the terminal of the evaluation glass plate by a load ring. The load was continuously increased so that the displacement of the glass plate was 1 mm / min, and the load at which the glass plate broke was taken as the breaking strength. A total of five samples were measured for each condition, and the average value was used as data on the breaking strength before and after terminal attachment.
[0139] [Examples 11-17, Examples 21-27] (Production of evaluation glass plate with conductor (evaluation glass plate 1)) An evaluation glass plate with a conductor (evaluation glass plate 1, no light-shielding layer) was produced in the same manner as described below in [Production of evaluation glass plate with light-shielding layer and conductor (evaluation glass plate 2)], except that a conductive paste layer was formed directly on one surface of the glass plate without forming a ceramic paste layer.
[0140] (Production of evaluation glass plate with light-shielding layer and conductor (evaluation glass plate 2)) A 100 mm x 100 mm square unreinforced glass plate ("VFL" manufactured by AGC) with a thickness of 2 mm was prepared. A ceramic paste for forming a light-shielding layer containing a black pigment and glass frit was applied onto one surface of the glass plate and dried to form a ceramic paste layer. The drying conditions were 120°C and about 10 minutes. Ceramic paste A was used as the ceramic paste.
[0141] Next, a silver-containing paste for forming a conductor, which contains silver powder and glass frit, was applied onto the ceramic paste layer and dried at 120° C. for about 10 minutes to form a conductive paste layer. In Examples 11 to 17, silver-containing paste A was used as the silver-containing paste. In Examples 21 to 27, silver-containing paste B was used as the silver-containing paste. The vehicle content of both silver-containing pastes A and B was 10 to 45% by mass.
[0142] Next, the ceramic paste layer and the conductive paste layer were fired. The temperature was raised from room temperature (20-25°C) to 615°C at a rate of about 180°C / min, fired at 615°C for 3 minutes, and then naturally cooled to room temperature (20-25°C) (pre-firing). Next, the temperature was raised to 600°C at a rate of about 180°C / min, fired at 600°C for 3 minutes, and naturally cooled to room temperature (20-25°C) (main firing). In this way, the light-shielding layer and the conductor were formed. The planar shape of the light-shielding layer was a square of 52 mm × 52 mm, and its center and diagonal were aligned with the center and diagonal of the glass plate. The thickness of the light-shielding layer was about 15 μm. The planar shape of the conductor was a square of 50 mm x 50 mm, and its center and diagonal were aligned with the center and diagonal of the glass plate. The thickness of the conductor formed using silver-containing paste A was 8.2 μm. The thickness of the conductor formed using silver-containing paste B was 6.2 μm. In this manner, a glass plate for evaluation having a light-shielding layer and a conductor (glass plate for evaluation 2) was produced.
[0143] (Conductor polishing) In each of Examples 12 to 17 and Examples 22 to 27, the conductors of the evaluation glass plates 1 and 2 were subjected to surface polishing using an abrasive eraser, metal fiber, or an electric cutting tool (hand grinder). The polishing conditions were as follows. The physical properties of the conductors were evaluated before and after polishing.
[0144] <Abrasive eraser> The abrasive eraser used was SEED's "Sand Eraser for Ink and Ballpoint Pens" (grit: #220 equivalent). The abrasive eraser was held with the fingers of one hand, pressed against the surface of the conductor, and moved horizontally from one end of the conductor to the other. This operation was repeated a total of eight times.
[0145] <Metal fiber> As the metal fiber, steel wool (count: #000, fiber center diameter: 14 μm, 1 g) manufactured by Bonstar was used. The fingers of one hand held the steel wool, pressed it against the surface of the conductor, and moved it horizontally from one end of the conductor to the other, repeating this process 24 times in total.
[0146] <Electric cutting tool (hand grinder)> The electric cutting tool (hand grinder) used was a "Luter (registered trademark)" manufactured by Nippon Seimitsu Kikai Kogyo Co., Ltd. The tip tool used was an angle tool consisting of a rubber pad and an abrasive disk attached to it. Four types of abrasive disks were used: cushion disk #1200, cushion disk #800, cushion disk #400, and cushion disk #240. In the example where silver-containing paste A was used as the silver-containing paste, the rotation speed of the grinder was 2000 rpm and the polishing time was 10 seconds. In the example in which silver-containing paste B was used as the silver-containing paste, the rotation speed of the grinder was 2000 rpm and the polishing time was 5 seconds.
[0147] <Solder joint> In each example, a brass crimp terminal consisting of a cylindrical power supply member joint into which the tip of the wire harness (exposed conductor portion) is inserted and a bridge-shaped portion having solder joints at both ends as shown in Figure 4 was joined to the conductor of evaluation glass plates 1 and 2 using SnAg-based lead-free solder (Sn: 98% by mass, Ag: 2.0% by mass, melting point: approximately 220°C). The specific method is as follows. An appropriate amount of lead-free solder was placed on the tip of a soldering iron and heated to melt it. This solder is called pre-solder. A 0.05g lead-free solder chip was attached to each solder joint of the terminal. This terminal was placed on the terminal joint of the conductor. In this state, the tip of a soldering iron set to 300℃ was pressed against the solder joint of the terminal to heat and melt the lead-free solder chip. The soldering iron was then removed from the terminal and the lead-free solder was allowed to solidify by natural cooling. After one hour had elapsed from the time when the terminals were joined onto the conductor via lead-free solder, the breaking strength of the evaluation glass plates 1 and 2 after the terminals were attached was measured.
[0148] [Evaluation results for Examples 11-17 and 21-27] The main experimental conditions and evaluation results of Examples 11 to 17 are shown in Tables 1-1 and 1-2. The main experimental conditions and evaluation results of Examples 21 to 27 are shown in Tables 2-1 and 2-2.
[0149] [Table 1-1]
[0150] [Table 1-2]
[0151] [Table 2-1]
[0152] [Table 2-2]
[0153] A comparison with Examples 11 and 21 revealed that, under the same conditions except for the type of silver-containing paste, the conductor obtained using silver-containing paste A had a smaller surface roughness (Ra) and a larger porosity when compared in an unpolished state than the conductor obtained using silver-containing paste B. The conductor of Example 11 obtained using silver-containing paste A had a porosity of 16.0% in the unpolished state, which was similar to the porosity of the conductive tracks of Examples 2 and 3 in the [Examples] section of Patent Document 2.
[0154] From the results of Examples 11 and 21, it was found that, when compared in an unpolished state under the same conditions except for the presence or absence of a light-shielding layer, evaluation glass plate 2 (with light-shielding layer) had a lower fracture strength after terminal attachment than evaluation glass plate 1 (without light-shielding layer). It is presumed that, when the paste is fired with a light-shielding layer, some of the glass frit components contained in the material for forming the light-shielding layer migrate to the surface of the conductor, resulting in more glass frit components being present on the surface of the conductor, and thus reducing the bonding strength between the conductor and the solder.
[0155] In Examples 12 to 17 in which the surface of the conductor was polished, the porosity, film thickness, and arithmetic mean surface roughness (Ra) of the conductor were reduced compared to Example 11 in which the surface of the conductor was not polished. In Examples 22 to 27 in which the surface of the conductor was polished, the porosity, film thickness, and arithmetic mean surface roughness (Ra) of the conductor were reduced compared to Example 21 in which the surface of the conductor was not polished.
[0156] In Examples 12 to 17, in which the surface of the conductor was polished, the porosity of the conductor could be reduced to 10% or less, compared to Example 11, in which the surface of the conductor was not polished. It is presumed that the voids in the conductor are filled by polishing. An example of the porosity measurement is shown in FIG. 10A to FIG. 10C. The two images on the left side of FIG. 10A show two of the three cross-sectional SEM images of the conductor obtained in Example 11, and the two images on the right side of FIG. 10A show the image processing results of the two cross-sectional SEM images on the left side and the measurement results of the porosity. The two images on the left side of FIG. 10B show two of the three cross-sectional SEM images of the conductor obtained in Example 14, and the two images on the right side of FIG. 10B show the image processing results of the two cross-sectional SEM images on the left side and the measurement results of the porosity. The two images on the left side of FIG. 10C show two of the three cross-sectional SEM images of the conductor obtained in Example 15, and the two images on the right side of FIG. 10C show the image processing results of the two cross-sectional SEM images on the left side and the measurement results of the porosity.
[0157] In the conductor obtained in Example 21 (without polishing, with light-shielding layer), many large voids were observed on both the surface and cross section, but in the conductor obtained in Example 22 (with polishing, with light-shielding layer), it was confirmed that the voids had disappeared or been significantly reduced on both the surface and cross section. It is presumed that by polishing the surface of the conductor, the silver is stretched and the voids are filled.
[0158] Examples 12 to 17, in which the surface of the conductor was polished, satisfied the following conditions 1 and 2, and in both evaluation glass plate 1 (without light-shielding layer) and evaluation glass plate 2 (with light-shielding layer), the breaking strength after terminal attachment was improved compared to Example 11. Examples 22 to 27, in which the surface of the conductor was polished, satisfied the following conditions 1 and 2, and in both evaluation glass plate 1 (without light-shielding layer) and evaluation glass plate 2 (with light-shielding layer), the breaking strength after terminal attachment was improved compared to Example 21.
[0159] (Condition 1) The ratio of the arithmetic mean surface roughness (Ra) of the terminal joint portion of the conductor after polishing to that before polishing is 5 to 80%. (Condition 2) The rate of decrease in film thickness at the terminal bonding portion of the conductor after polishing is 4 to 40% compared to before polishing.
[0160] [Examples 31-35] In Example 31, an evaluation glass plate with a light-shielding layer and a conductor (evaluation glass plate 2, conductor (unpolished) / light-shielding layer / glass plate) was produced in the same manner as in Example 21, except for changing the type of ceramic paste used to form the light-shielding layer. In Example 32, a glass plate for evaluation with a light-shielding layer and a conductor (evaluation glass plate 2, conductor (polished) / light-shielding layer / glass plate) was produced in the same manner as in Example 22, except for changing the type of ceramic paste used to form the light-shielding layer. In each of Examples 33 to 35, a glass plate for evaluation with a light-shielding layer and a conductor (evaluation glass plate 2, conductor (polished) / light-shielding layer / glass plate) was produced in the same manner as in Example 32, except that the grit size of the polishing eraser was changed. In these examples, ceramic paste B was used as the ceramic paste for forming the light-shielding layer. The abrasive erasers used in Examples 32 to 35 are as follows. Example 32: SK-11 "Abrasive Eraser" (grit: #220), Example 33: "Sabitol" (grit: #320) manufactured by Chukyo Kenma Co., Ltd. Example 34: Stella Block (grit: #500) made by Okasugi Co., Ltd. Example 35: SK-11 "Abrasive eraser" (grit: #1000).
[0161] The conductors obtained in each of Examples 31 to 35 were soldered in the same manner as in Examples 21 and 22, and the breaking strength of the evaluation glass plate 2 after terminal attachment was measured. The main experimental conditions and evaluation results of Examples 31 to 35 are shown in Table 3. Examples 32 to 35 in which the surface of the conductor was polished had improved breakdown strength after terminal attachment compared to Example 31 in which the surface of the conductor was not polished.
[0162] [Table 3]
[0163] [Example 41] A glass plate for evaluation (glass plate for evaluation 2) with a light-shielding layer and a conductor was manufactured in the same manner as in Example 21, except that the ceramic paste C and the silver-containing paste B were used and the firing conditions were changed. The firing conditions were as follows: the temperature was raised from room temperature (20 to 25°C) to 600°C at a rate of 180°C / min, and the plate was fired at 600°C for about 4 minutes, and then naturally cooled to room temperature (20 to 25°C). As in Example 21, no surface polishing of the conductor was performed. An attempt was made to perform solder bonding on the conductor of the obtained evaluation glass plate 2 in the same manner as in Example 21, but solder bonding could not be performed because the wettability of the lead-free solder to the surface of the conductor on the light-shielding layer formed using ceramic paste C was poor.
[0164] [Examples 42-45] In each of Examples 42 to 45, a glass plate for evaluation having a light-shielding layer and a conductor (glass plate for evaluation 2) was produced in the same manner as in Example 41. The surface of the conductor of the obtained evaluation glass plate 2 was polished using an abrasive eraser. The abrasive eraser was held with the fingers of one hand and pressed against the surface of the conductor, and moved horizontally from one end of the conductor to the other. This operation was repeated six times in total. The abrasive erasers used in each example are as follows: Example 52: SK-11 "Abrasive Eraser" (grit: #220), Example 53: "Sabitol" (grit: #320) manufactured by Chukyo Kenma Co., Ltd. Example 54: SK-11 "Abrasive Eraser" (grit: #1000), Example 55: SK-11 "Abrasive eraser" (grit: #2000). The conductor of the obtained evaluation glass plate 2 was soldered in the same manner as in Example 22. In these examples, the wettability of the lead-free solder to the surface of the conductor on the light-shielding layer formed using the ceramic paste C was improved by surface polishing, and soldering could be performed well. The fracture strength of the evaluation glass plate 2 after the terminals were attached was measured.
[0165] [Evaluation results of Examples 41 to 45] The main experimental conditions and evaluation results of Examples 41 to 45 are shown in Table 4, and FIGS. 11A and 11B.
[0166] [Table 4]
[0167] In Example 41, in which the surface of the conductor was not polished, the stress value of the terminal joint of the conductor was +45 MPa. It was confirmed that the terminal joint of the unpolished conductor was subjected to tensile stress. The breaking strength of the obtained evaluation glass plate 2 before the terminal attachment was measured and found to be 65 MPa. In Examples 41 to 45, in which the surface of the conductor was polished, the stress value of the terminal joint of the conductor after surface polishing was -50 to -20 MPa, and it was confirmed that at least the surface of the terminal joint of the conductor after surface polishing became a compressive stress part where compressive stress was applied. In these examples, the fracture strength after terminal attachment was high and good.
[0168] The present invention is not limited to the above-described embodiment and examples, and the design can be appropriately modified without departing from the spirit of the present invention. [Explanation of symbols]
[0169] 1, 2: vehicle windshield, 10, 50: laminated glass, 11, 13: glass plate, 11E: exposed portion, 11X, 13X: glass plate with terminal, 11Y, 13Y: glass plate with conductor, 12: intermediate film, 13N: notch, 20, 40, 80: conductor, 20B, 80B: power supply electrode, 20E: exposed portion, 20L, 80L: heating wire, 20P, 80P: polished portion, 20NP, 80NP: non-polished portion, 20T, 80T: terminal joint, 20CS, 80CS: compressive stress portion, 101: lead-free solder, 102: terminal, 102A: power supply member joint, 102B: solder joint, 103: power supply member, BL: light-shielding layer, OP: optical device mounting area, TP: light-transmitting portion.
Claims
1. The laminated glass includes a plurality of glass sheets bonded together via an interlayer film, The laminated glass is a vehicle windshield comprising: the glass plate; a terminal-attached glass plate having a conductor formed on one surface of the glass plate, the conductor being made of a material containing silver and glass frit and having a terminal joint portion to which a terminal is joined; and a terminal joined onto the terminal joint portion of the conductor via lead-free solder; the electrical conductor includes an electrical function or is electrically connected to an electrical function; the conductor includes a power supply portion for supplying power to the electrical function portion, the power supply portion including the terminal joint portion; At least a surface of the terminal joint portion is a compressive stress portion.
2. The compressive stress portion was measured using a micro-part X-ray stress measuring device. 2 2. The vehicle windshield according to claim 1, wherein a stress value measured by a ψ method is −20 MPa or less.
3. The compressive stress portion was measured using a micro-part X-ray stress measuring device. 2 3. The vehicle windshield according to claim 2, wherein the stress value measured by the ψ method is −50 to −20 MPa.
4. The vehicle windshield according to claim 1 or 2, wherein the conductor has a polished portion on a surface of a region including the terminal joint portion.
5. The vehicle windshield according to claim 4 , wherein the conductor has an unpolished portion on a surface of the area not including the terminal joint portion.
6. the glass plate with terminals has a light-shielding layer between the glass plate and the terminal joint portion of the conductor, The vehicle windshield according to claim 1 , wherein the light-shielding layer contains a black pigment and a glass frit.
7. 3. The vehicle windshield according to claim 1, wherein the glass plate with terminals has an exposed portion that is not covered by the glass plate facing the terminals via the intermediate film, the conductor is formed on a side of the glass plate with terminals facing the intermediate film, and the terminal joint portion of the conductor is formed on the exposed portion of the glass plate with terminals.
8. 3. The vehicle windshield according to claim 1, wherein in the laminated glass, the conductor is formed on a side of the glass plate with terminals opposite to a side of the interlayer film.
9. the glass plate with terminals has, in a plan view, an optical device mounting region in which an optical device is mounted, a light-transmitting portion located within the optical device mounting region and through which incident light from the outside to the optical device and / or emitted light from the optical device passes, and a light-shielding layer surrounding at least a portion of the light-transmitting portion in a plan view, 9. The vehicle windshield according to claim 8, wherein the conductor includes a heating wire formed inside the light-transmitting portion, the power supply portion formed outside the light-transmitting portion, and a connection wiring formed outside the light-transmitting portion and connecting the heating wire and the power supply portion.
10. 3. The vehicle windshield according to claim 1, wherein a power supply member made of a round or foil conductor is fixed to the terminal.
11. A step (S2) of applying a silver-containing paste containing silver and glass frit, which are materials for the conductor, onto the glass plate, which is a material for the glass plate with terminals; A step (S3) of firing the glass plate coated with the material for the conductor to form the conductor including the terminal joint portion; A step (S5) of plastically deforming at least a surface of a region including the terminal joint portion of the conductor; 3. The method for manufacturing a vehicle windshield according to claim 1, further comprising: a step (S6) of joining the terminal via lead-free solder onto the terminal joining portion, at least the surface of which has been plastically deformed.
12. The method for manufacturing a vehicle windshield according to claim 11, wherein the step (S5) is a step of polishing a surface of a region including the terminal joint portion of the electric conductor.
13. In the laminated glass, the glass sheet with terminal has an exposed portion that is not covered by the glass sheet facing the terminal with the interlayer film interposed therebetween, the conductor is formed on the glass sheet with terminal on the interlayer film side, and the terminal connection portion of the conductor is formed on the exposed portion of the glass sheet with terminal, The method for manufacturing a vehicle windshield according to claim 11, further comprising a step (S4) of bonding the plurality of glass plates together via the intermediate film between the step (S3) and the step (S5).
14. In the laminated glass, the conductor is formed on a side of the glass plate with terminals opposite to a side of the interlayer film, The method for manufacturing a vehicle windshield according to claim 11, further comprising a step (S4) of bonding the plurality of glass plates together via the intermediate film between the step (S3) and the step (S5).
15. the glass plate with terminals has a light-shielding layer between the glass plate and the terminal joint portion of the conductor, Prior to the step (S2), a step (S1) is provided for applying a ceramic paste containing a black pigment and a glass frit, which are materials for the light-shielding layer, onto the glass plate, which is a material for the glass plate with terminals; The method for manufacturing a vehicle windshield according to claim 11, wherein in the step (S3), a material for the light-shielding layer is fired to form the light-shielding layer.
Citation Information
Patent Citations
Glass plate module
JP2021018932A
Glass article with conductive film formed thereon and method for manufacturing same
WO2006132319A1